Fostering a cosmopolitan scholarly culture - Abd Razak, Dzulkifli (2005)
Other than Spain, southern Italy which was ruled by the Norman kings of Sicily, also assisted in diffusing Andalusian culture to other parts of Italy and central Europe as well. The continuous intellectual intercourse between the two Norman states of England and Sicily was instrumental in bringing many elements of Muslim culture to as far as distant Britain. A case in point was the work of the greatest surgeon of the Middle Ages, Abu alQasim alZahrawi, (known in the West as Abulcasis or AlBucasis), who was born near Cordoba. His work was used as a standard reference work in the subject in all universities of Europe for over 500 years. His book, AlTasrif, was translated into Latin and became the leading medical text in European universities during the later Middle Ages.